2022
DOI: 10.1007/s10554-021-02403-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of non-valvular atrial fibrillation with left atrial appendage thrombus who are undergoing appropriate oral anticoagulation therapy

Abstract: We investigated the characteristics of patients with non-valvular atrial fibrillation (NVAF) and left atrial (LA) appendage (LAA) thrombus who had been given appropriate oral anticoagulation therapy. Methods:We studied 737 NVAF patients who were scheduled for catheter ablation or electrical cardioversion. All patients received appropriate oral anticoagulation therapy for at least 3 weeks prior to echocardiography in accordance with the guidelines. Whether LAA thrombus was present or absent on transesophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…These studies were published between 2016 and 2022. Among the studies, four were conducted in Poland [ 27 , 29 , 30 , 33 ], two were conducted in Japan [ 25 , 32 ], two were conducted in the United States [ 24 , 28 ], and one was conducted each in the EU [ 26 ], Germany [ 31 ], Canada [ 21 ], Turkey [ 23 ], and Italy [ 22 ]. The selected studies were mostly conducted in Western countries, and only two were conducted in an Asian population (Japan).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies were published between 2016 and 2022. Among the studies, four were conducted in Poland [ 27 , 29 , 30 , 33 ], two were conducted in Japan [ 25 , 32 ], two were conducted in the United States [ 24 , 28 ], and one was conducted each in the EU [ 26 ], Germany [ 31 ], Canada [ 21 ], Turkey [ 23 ], and Italy [ 22 ]. The selected studies were mostly conducted in Western countries, and only two were conducted in an Asian population (Japan).…”
Section: Resultsmentioning
confidence: 99%
“…The selected studies were mostly conducted in Western countries, and only two were conducted in an Asian population (Japan). Six studies were prospective [ 21 , 22 , 23 , 26 , 29 , 33 ], and seven were retrospective [ 24 , 25 , 27 , 28 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8-12 Furthermore, a recent study by Shiraki et al found that LAVI as a parameter of transthoracic echocardiography in multivariate logistic regression analysis was the only independent predictor of LAA thrombus formation for 737 patients with non-valvular AF who had received appropriate oral anticoagulation therapy. 11 Shiraki et al also showed that the prevalence of LAA thrombus formation in AF patients with LAVI ≥50 mL/m 2 was high as 8.7%. 11 Thus, transcatheter or surgical LAA occlusion may be another therapeutic strategy to avoid thromboembolism in AF patients with a larger LAVI.…”
Section: Discussionmentioning
confidence: 95%
“…4 In addition, LA enlargement in AF patients is associated with the development of HF or thromboembolism. [5][6][7][8][9][10] Mitral regurgitation (MR), and a recently recognized disease entity known as atrial functional mitral regurgitation (AFMR), occurs due to mitral annular dilatation with LA enlargement in AF patients and is closely related to prognosis. [7][8][9][10] Catheter ablation is a currently well-established treatment for AF patients to prevent adverse events such as the development of HF or stroke.…”
Section: Introductionmentioning
confidence: 99%